OC 8721 WANECAM II – a clinical trial programme to assess safety, efficacy and transmission-blocking properties of a new antimalarial KAF156 (ganaplacide) in uncomplicated malaria in west and central africa. (24th April 2019) - Djimde, Abdoulaye; ,; Grobusch, Martin P; Zoleko Manego, Rella; Mombo-Ngoma, Ghyslain; Picot, Stephane; Sagara, Issaka; Sutherland, Colin; Kone, Aminatou; Doumbo, Ogobara K; Pedro Gil, Jose; Björkman, Anders; et al.
Abstract : Background: Despite major progress in the past decade, malaria remains a major public health problem in sub-Saharan Africa. West and Central Africa account for nearly 2/3 of the burden currently attributable to falciparum malaria. Artemisinin-based combination therapies (ACT) are a cornerstone of our strategy for controlling and eventually eliminating malaria. However, reduced responsiveness/resistance to artemisinin derivatives and to ACTs, an increasing problem in South-East Asia is a major concern. It is of utmost importance to develop new antimalarial drugs from novel chemical classes that can replace ACTs. KAF156, an imidazolepiperazine, is a leading candidate in the antimalarial drug development pipeline. Combination of KAF156 with a Solid Dispersion Formulation of lumefantrine (LUM-SDF) is expected to be fast acting, fully curative, improve patient adherence and can potentially reduce malaria transmission. Methods: WANECAM II proposes to advance the clinical development of KAF156 through clinical trials in adults and children, with integrated capacity building and infrastructure development activities. The trial programme will be undertaken in the context of networking, team-building, leadership development and community engagement schemes that will involve intra-European, European-African and intra-African collaborative activities. WANECAM II will accelerate the clinical study of children less than 2 years of age which are the key target for new antimalarial treatments. Results: By the end of the project, the results are expected to contribute to the registration of KAF156/LUM-SDF through stringent regulatory health authorities, increase biomedical research capacity in the consortium and effectively promote networking among the respective teams. A new clinical research team in Niger, a grossly underrepresented country in the African research landscape, will be developed and further increase capacity and infrastructure in the consortium. Conclusion: Providing a new antimalarial drug combination that does not contain an artemisinin derivative and is effective against resistant P. falciparum strains as well as gametocytes and that is likely to be taken in 3 or fewer single doses will be a major advance in the field. The new combination of KAF156 with LUM-SDF is expected to provide such major advance upon successful conclusion of the WANECAM II project.